INDEKS MINAT BACA MASYARAKAT; STUDI KASUS DI KOTA KEDIRI, JAWA TIMUR - Muhammad Rosyihan Hendrawan; Fatich Idamatul Machsunin; Eric Budi Maulana (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2022)
To improve the literacy rate of the population, the government, through the Ministry of Education and Culture, has initiated the National Literacy Movement (GLN) program since 2016, consisting of the School Literacy Movement (GLS), Family Literacy Movement, and Community Literacy Movement. motion exists. The National Literacy Movement has encouraged the growth of a reading culture. The purpose of habituation is to increase interest in reading and improve reading skills so that knowledge can be acquired better. The researchers chose Kediri city in East Java. Kediri City is a service city, a city with a thriving trade and service industry. The purpose of this study is to determine how to develop a test of variables and indicators that represent reading habits and suitable indicators for measuring levels of reading habits. Reading habits in Kediri city. East Java. According to the findings, the Kediri City Reading Interest Index is in the top category with 79.7, the score he is composed of four index dimensions. Each index value mentioned for the city of Kediri is a skill dimension index of 93.9. An Access Dimension Index of 65.3 belongs to the high category. 90.3 Very High Categorical Alternate Dimension Index. The cultural dimension index is 69.2, which is in the high category. The nine years of obligatory schooling are a great contribution to Kediri Municipality's efforts to increase community literacy, and electronic reading material for smartphones and computers (laptops, PCs, tablets, and/or tablets) that supports Latin letter reading and writing is also available. According to the aforementioned statistics, there is truly very great potential for local communities to independently provide print reading and Internet networks, as well as the use of computer devices that bridged the majority of the access to multiple reading sources. Therefore, we must concentrate on promoting more streamlined, secure, and dependable access.